2010
DOI: 10.1258/jms.2010.009101
|View full text |Cite
|
Sign up to set email alerts
|

Endorsement by the Primary Care Practitioner Consistently Improves Participation in Screening for Colorectal Cancer: A Longitudinal Analysis

Abstract: Objectives To investigate the effect of general practice (GP) and general practitioner (GPR) endorsement for faecal occult blood test (FOBT)-based screening on maintenance of participation in screening over four successive screening rounds. Setting South Australian residents aged !50 years. Methods Random selection of four groups (n ¼ 600 per group): one from the Commonwealth electoral roll (ER) and three from the combined patient lists of two collaborating GPs (GP1, GP2, GP3). Subjects were mailed offers to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 14 publications
4
44
3
Order By: Relevance
“…Consistent with other studies in Australia (Cole, Smith, Wilson, Turnbull, Esterman, & Young, 2007;Cole, Young, & Byrne, 2002;Zajac, Whibley, Cole, Byrne, Guy, Morcom et al, 2010) and internationally (Brouse et al, 2003;Damery, Clifford, & Wilson, 2010;Federici, Rossi, Bartolozzi, Farchi, Borgia, & Guastcchi, 2006;Ferreira, Dolan, Fitzgibbon, Davis, Gorby, Ladewski et al, 2005;Klabunde, Frame, Meadow, Jones, Nadel, & Vernon, 2003;Myers, Sifri, Hyslop, Rosenthal, Vernon, Cocroft et al, 2007;Rossi et al, 2005;Vernon, 1997), our study also revealed that doctor's recommendation and endorsement is one of the strongest predictors of CRC screening. Studies in the UK which use sigmoidoscopy as the method of CRC screening also highlight the importance of GP endorsement and recommendation (Brotherstone, Vance, Edwards, Miles, Robb, Evans et al, 2007;McCaffery, Borril, Williamson, Taylor, Sutton, Atkin et al, 2001;Power, Van Jaarsveld, McCaffery, Miles, Atkin, & Wardle, 2008;Robb, Power, Kralj-Hans, Edwards, Vance, Atkin et al, 2010;Sutton, Wardle, Taylor, McCaffery, Williamson, Edwards et al, 2000), although the relevance of these studies may be questioned due to the different type of CRC screening test used.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies in Australia (Cole, Smith, Wilson, Turnbull, Esterman, & Young, 2007;Cole, Young, & Byrne, 2002;Zajac, Whibley, Cole, Byrne, Guy, Morcom et al, 2010) and internationally (Brouse et al, 2003;Damery, Clifford, & Wilson, 2010;Federici, Rossi, Bartolozzi, Farchi, Borgia, & Guastcchi, 2006;Ferreira, Dolan, Fitzgibbon, Davis, Gorby, Ladewski et al, 2005;Klabunde, Frame, Meadow, Jones, Nadel, & Vernon, 2003;Myers, Sifri, Hyslop, Rosenthal, Vernon, Cocroft et al, 2007;Rossi et al, 2005;Vernon, 1997), our study also revealed that doctor's recommendation and endorsement is one of the strongest predictors of CRC screening. Studies in the UK which use sigmoidoscopy as the method of CRC screening also highlight the importance of GP endorsement and recommendation (Brotherstone, Vance, Edwards, Miles, Robb, Evans et al, 2007;McCaffery, Borril, Williamson, Taylor, Sutton, Atkin et al, 2001;Power, Van Jaarsveld, McCaffery, Miles, Atkin, & Wardle, 2008;Robb, Power, Kralj-Hans, Edwards, Vance, Atkin et al, 2010;Sutton, Wardle, Taylor, McCaffery, Williamson, Edwards et al, 2000), although the relevance of these studies may be questioned due to the different type of CRC screening test used.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the UK which use sigmoidoscopy as the method of CRC screening also highlight the importance of GP endorsement and recommendation (Brotherstone, Vance, Edwards, Miles, Robb, Evans et al, 2007;McCaffery, Borril, Williamson, Taylor, Sutton, Atkin et al, 2001;Power, Van Jaarsveld, McCaffery, Miles, Atkin, & Wardle, 2008;Robb, Power, Kralj-Hans, Edwards, Vance, Atkin et al, 2010;Sutton, Wardle, Taylor, McCaffery, Williamson, Edwards et al, 2000), although the relevance of these studies may be questioned due to the different type of CRC screening test used. Nevertheless, If the potential benefits of bowel cancer screening are to be realised, GPs must be actively engaged (Damery et al, 2010;Klabunde, Lanier, Breslau, Zapka, Fletcher, Ransohoff et al, 2007;Zajac et al, 2010). Within our study, the engagement of and endorsement by GPs and nurse practitioners in the program and offering the screening test through them were highly recommended by the Anglo-Australian participants.…”
Section: Discussionmentioning
confidence: 97%
“…This contrasts with previous research that has highlighted the importance of recommendations from health professions in the decision to screen for CRC (Costanza et al, 2005;Holt et al, 2009;Jones et al, 2010;Vedel et al, 2011;Zajac et al, 2010). However, the participants did identify indirect influences on their decision to screen, such as knowing others with CRC and media reports on the topic.…”
contrasting
confidence: 90%
“…Our national trial of GPE significantly increased uptake overall. The effect size was smaller than in many previous studies, 36,196,216,217 but this was probably because most of those had used letters directly from the GP or had an individual GP's signature on the letter. In the NHS BCSP, all invitation letters come from the hubs; therefore, the only practical option was to include a banner noting that the individual's general practice supported the programme, but without individual GPs' names or signatures.…”
Section: Discussioncontrasting
confidence: 65%